2022
DOI: 10.1002/rob.22060
|View full text |Cite
|
Sign up to set email alerts
|

Fast and incremental loop closure detection with deep features and proximity graphs

Abstract: In recent years, the robotics community has extensively examined methods concerning the place recognition task within the scope of simultaneous localization and mapping applications. This article proposes an appearance‐based loop closure detection pipeline named “Fast and Incremental Loop closure Detection (FILD++). First, the system is fed by consecutive images and, via passing them twice through a single convolutional neural network, global and local deep features are extracted. Subsequently, a hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…The term N/A denotes that the corresponding information is not available from any cited source. Furthermore, for the case of FAB‐MAP 2.0 [38] and DBoW2 [40] along with FILD [52] where no actual measurements are provided regarding the used datasets, the presented results are obtained from the setup described in [55, 81], respectively. Most of the approaches (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The term N/A denotes that the corresponding information is not available from any cited source. Furthermore, for the case of FAB‐MAP 2.0 [38] and DBoW2 [40] along with FILD [52] where no actual measurements are provided regarding the used datasets, the presented results are obtained from the setup described in [55, 81], respectively. Most of the approaches (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…-259 represent an image and determine potentially revisited locations [46][47][48][49][50][51][52][53][54][55][56]. These layers are originally trained for object recognition; thus, they are tightly bounded to their learning example attributes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ma et al (2021) proposed a tailormade feature matching method based on locality consistency to check the geometric relationship of detections. As a de-facto standard post-verification procedure, scholars widely apply epipolar check which estimates the fundamental matrix between features across images based on the random sample consensus (RANSAC) (Fischler & Bolles, 1981) procedure and then validates the detection by the number of feature inliers (An et al, 2022;Galvez-López & Tardos, 2012;Garcia-Fidalgo & Ortiz, 2017;Galvez-López & Tardós, 2011;Lynen et al, 2017;Tsintotas et al, 2018Tsintotas et al, , 2019. It works properly in most scenes but fails when estimation is unreliable due to dominated outliers or incorrect parametric model.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, motivated by the success of deep CNN in other computer vision tasks, many novel learned features (Arandjelovi et al, 2018; DeTone et al, 2018; Dusmanu et al, 2019; Noh et al, 2017; Sarlin et al, 2019) have been proposed and shown improved robustness against varying illuminations and viewpoints than traditional counterparts. Some scholars have begun to use CNN‐based features to perform loop detection, such as NetVLAD (Arandjelovi et al, 2018), DELF (Noh et al, 2017), HF‐Net (Sarlin et al, 2019), and other CNN‐based features (An et al, 2022; Hou et al, 2018; Kenshimov et al, 2017; Lopez‐Antequera et al, 2017; Memon et al, 2020; Yue et al, 2019).…”
Section: Related Workmentioning
confidence: 99%